Preparation method and application of sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicating film
Through the preparation method of sodium alginate (SA)/PCN-225/Eu(DBM) 3Bpy composite indicator film, the problems of high cost, time-consuming and insufficient safety in food freshness detection are solved, and the detection effect of high sensitivity, high safety and reusable is achieved.
Patent Information
- Application Number
- CN202411729008.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art has problems such as high cost, time-consuming and complex operation in food freshness detection, and traditional fluorescent sensors have shortcomings in terms of safety and reusability.
The preparation method of sodium alginate (SA)/PCN-225/Eu(DBM) 3Bpy composite indicator film was adopted to prepare PCN-225 powder by hydrothermal method, and the composite indicator film was prepared by casting method, combining crosslinking reaction to improve the mechanical properties and water resistance of the film.
It realizes high sensitivity, high safety and reusable food freshness detection, which can detect ammonia and food freshness in real time, and has broad application prospects.
Smart Images

Figure CN119529344A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of analytical technology, and specifically relates to a preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film. Background Art
[0002] During the transportation and storage of food, due to exogenous microorganisms and endogenous enzymatic hydrolysis, it will cause corruption and deterioration, resulting in a decrease in food freshness. When microorganisms act on meat and meat products, volatile gases such as ammonia, dimethylamine, methylamine, trimethylamine (TMA) and other biogenic amine components will be produced, which are collectively referred to as total volatile basic nitrogen (TVB-N). Excessive intake of TVB-N by the human body can cause food poisoning and threaten people's life safety. Therefore, it is of great significance to develop a method for detecting TVB-N and then realize the freshness detection of food. At present, freshness detection technologies such as chromatography, spectroscopy and mass spectrometry can be applied to food freshness detection, but these technologies are too expensive, time-consuming, require professional technicians to operate, and cannot meet the needs of consumers. Compared with detection methods such as chromatography, spectroscopy and mass spectrometry, sensor detection technology has the advantages of accuracy, simplicity, speed and low cost, and has become the future development trend of biogenic amine and food freshness detection. Among them, fluorescence sensing technology is one of the common biogenic amine and food freshness sensing detection technologies. A fluorescent sensor is a device that can specifically identify biogenic amines such as ammonia produced during food spoilage and convert their concentrations into fluorescent signals that are easy to detect. It can realize qualitative and quantitative detection of biogenic amines and food freshness, and has important application prospects in the field of food freshness detection.
[0003] In recent decades, fluorescent indicator films based on fluorescence sensing technology have attracted the attention of many researchers. The detection process of fluorescent indicator films is simple to operate, highly sensitive, selective, and can be qualitatively and quantitatively detected. It has the advantages of real-time, non-destructive, visual detection and low cost. Therefore, it has a wide range of applications and has become an important research direction in the field of food freshness detection. Meng et al. prepared an ammonia sensor film using anthocyanin as an indicator and cellulose nanocrystal-doped hydroxypropyl guar gum as a film matrix (ACS Sustainable Chem. Eng. 2020, 8, 26, 9731–9741). The detection limit of ammonia for this sensor is 1 μg / mL, and the sensor can be used to detect the freshness of fresh shrimp. Although a high loading amount of anthocyanin can be achieved by the immersion method, the indicator will seep out during the detection process, thus affecting the accuracy of the test results. Roy et al. developed a biogenic amine sensor based on aggregation-induced emission (AIE) switch-controlled colorimetric fluorescent probe tetraphenylethylene derivative aggregation-induced emission (ACSAppl.Mater.Interfaces 2019,11,50,47207–47217). The detection limit of the sensor for putrescine is as low as 4.3ppm, and the sensor is used to detect the spoilage of fish meat. However, this sensor is extremely unsafe and cannot be reused in food applications. Yuan Shuai et al. used β-glucan as the substrate, blended luminol in β-glucan, and pressed it into a fluorescent colorimetric indicator sheet with ammonia response (Yuan Shuai. Construction and application of fluorescent colorimetric indicator material for freshness of cold fresh meat based on β-glucan [D]. Inner Mongolia Agricultural University, 2023), and then applied it to the real-time detection of the freshness of cold fresh pork. When the pork is spoiled, the fluorescent colorimetric sheet with different luminol addition amounts changes from the initial blue fluorescence to black-blue fluorescence, and the fluorescence is almost quenched, realizing the freshness detection of pork. However, the fluorescence difference color of the indicator film under ultraviolet irradiation is small, and hydrogen peroxide needs to be added to make the fluorescence of the colorimetric film significantly different, which is too complicated. In addition, the fluorescent colorimetric film after adding hydrogen peroxide can only be used as a one-time indicator material and cannot be used multiple times. Therefore, it is of great significance to develop a preparation method for a composite indicator film with high sensitivity, safe ingredients, and can be used for biogenic amine and food freshness detection. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film, thereby achieving the purpose of the invention of preparing a highly sensitive composite indicator film that can be used for ammonia and food freshness detection.
[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film, characterized in that the preparation method comprises preparing PCN-225 powder by a hydrothermal method, activating PCN-225 powder, and preparing the sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film by a casting method;
[0006] The hydrothermal method is used to prepare PCN-225 powder. A certain mass of zirconium chloride (ZrCl4), meso-tetrakis (4-carboxyphenyl) porphine (H2TCPP) and benzoic acid are weighed respectively, and a certain volume of N,N-diethylformamide (DEF) and acetic acid are added. After ultrasonic dissolution, the mixture is dried to obtain PCN-225 powder.
[0007] The activated PCN-225 powder is washed with ethanol and acetone successively, and soaked in acetone, during which the acetone is replaced once, and then centrifuged and dried to obtain the activated PCN-225 powder.
[0008] The tape casting method for preparing the SA / PCN-225 / Eu(DBM)3Bpy composite indicator film comprises the following steps:
[0009] Step 1: prepare a PCN-225 solution, dissolve an appropriate amount of the activated PCN-225 powder in deionized water, and obtain a PCN-225 solution with a certain mass fraction after ultrasonic cleaning;
[0010] Step 2: Prepare PCN-225 / Eu(DBM)3Bpy solution, weigh a certain amount of organic europium Eu(DBM)3Bpy (DBM: dibenzoylmethane, Bpy: bipyridine) fluorescent powder, add it to the PCN-225 solution in step 1, and disperse it evenly by ultrasonication;
[0011] Step 3: Prepare SA / PCN-225 / Eu(DBM)3Bpy solution, weigh a certain amount of sodium alginate (SA) powder and add it to the PCN-225 / Eu(DBM)3Bpy solution in step 2, and add a small amount of glycerol, stir evenly, defoam and set aside;
[0012] Step 4: Prepare SA / PCN-225 / Eu(DBM)3Bpy film, take an appropriate amount of SA / PCN-225 / Eu(DBM)3Bpy solution, dry it at 40°C for 12h, and then dry the prepared SA / PCN-225 / Eu(DBM)3Bpy film;
[0013] Step 5: Prepare a high-strength, water-resistant SA / PCN-225 / Eu(DBM)3Bpy film. Place the SA / PCN-225 / Eu(DBM)3Bpy film described in step 4 into a calcium chloride solution with a certain mass fraction, take it out after a certain period of cross-linking reaction, and dry it to obtain a water-resistant SA / PCN-225 / Eu(DBM)3Bpy film.
[0014] Preferably, in step 1, the mass fraction of the PCN-225 solution is 0.004% to 0.02%.
[0015] Preferably, in step 3, the mass fraction of sodium alginate is 0.5% to 3%.
[0016] Preferably, in step 5, the mass fraction of the calcium chloride solution is 2%-10%.
[0017] Preferably, the activated PCN-225 powder is immersed in acetone for about 48 hours, during which the acetone is replaced every 12 hours.
[0018] The second object of the present invention is to provide an application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film prepared by the above-mentioned preparation method, characterized in that the application comprises the following steps:
[0019] Step 1: Place the SA / PCN-225 / Eu(DBM)3Bpy composite indicator film in the same environment as the object to be tested, place it in the air without direct contact with the object to be tested, and record the color change of the indicator film at a temperature of 20°C to 40°C;
[0020] Step 2: Take out the film in step 1 at regular intervals and photograph it under a fluorescent light to record the color changes.
[0021] Furthermore, in step 1, the analyte is one of ammonia water, dairy products, and meat-derived foods.
[0022] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are:
[0023] 1. The preparation method of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film provided by the present invention is adopted to achieve the invention purpose of preparing an indicator film with stable fluorescence, high pH response sensitivity and can be applied to ammonia and food freshness detection. The PCN-225 powder prepared by the hydrothermal method not only has excellent pH fluorescence response characteristics, but also has excellent thermal stability and stable fluorescence color.
[0024] 2. The sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film prepared by the casting method not only has good mechanical properties and color development properties after cross-linking reaction, but also the sodium alginate matrix has the advantages of being colorless, non-toxic, and degradable. It can not only effectively load PCN-225 powder, but also its excellent transparent properties can clearly present the fluorescent color of the film.
[0025] 3. The SA / PCN-225 / Eu(DBM)3Bpy indicator film prepared by the cast film method can detect the freshness of food in real time under ultraviolet light and sunlight. As milk and other dairy products, fresh shrimp, meat and other meat-derived foods continue to spoil, the indicator film can achieve real-time color response. Consumers can judge the freshness of milk and other dairy products, fresh shrimp, meat and other meat-derived foods in real time based on their naked eyes. It has broad application prospects in the field of food packaging.
[0026] 4. In addition to measuring the freshness of food, the ammonia content in ammonia water can also be measured separately. Using the SA / PCN-225 / Eu(DBM)3Bpy indicator film prepared by the cast film method, ammonia released from very low concentrations of ammonia water can also be detected, making it easier to take measures to avoid the harm of ammonia to the human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the preparation process of SA / PCN-225 / Eu(DBM)3Bpy composite indicator film;
[0028] Figure 2 Scanning electron microscope pictures of PCN-225 powder were obtained at different magnifications;
[0029] Figure 3 is the XRD spectrum of the prepared PCN-225 powder;
[0030] Figure 4 The infrared absorption spectra of PCN-225 powder and films with different components;
[0031] Figure 5 This is a photo of the color of PCN-225 powder dispersed in different pH solutions under UV light;
[0032] Figure 6 The fluorescence emission performance of PCN-225 powder dispersed in solutions with different pH values;
[0033] Figure 7 are the tensile strength and elongation at break of the films obtained at different PCN-225 mass fractions;
[0034] Figure 8The tensile strength and elongation at break of the film were obtained at different mass fractions of calcium chloride;
[0035] Fig. 9 This is a color comparison chart of the indicator film obtained at different PCN-225 mass fractions in air and 1% ammonia atmosphere under sunlight;
[0036] Fig.10 This is a color comparison chart of the indicator film obtained with different PCN-225 mass fractions in air and 1% ammonia atmosphere under ultraviolet light;
[0037] Fig.11 This is a color comparison chart of the films obtained with different calcium chloride mass fractions in air and 1% ammonia atmosphere under sunlight;
[0038] Fig.12 The following is a color comparison chart of the films obtained with different calcium chloride mass fractions in air and 1% ammonia atmosphere under ultraviolet light;
[0039] Fig.13 This is a color comparison diagram of the indicator film in different ammonia concentration atmospheres under ultraviolet light;
[0040] Fig.14 This is a color comparison chart of the indicator film placed in a bottle containing milk and fresh shrimp for a certain period of time under ultraviolet light at 20°C;
[0041] Fig.15 This is a color comparison chart of the indicator film after being placed in a bottle containing milk and fresh shrimp for a certain period of time under ultraviolet light at 40°C. DETAILED DESCRIPTION
[0042] The following is a detailed description of the embodiments and the attached Figure 1-15 , further illustrating the present invention.
[0043] Example 1 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0044] S1. Weigh 25 mg zirconium chloride (ZrCl4), 10 mg meso-tetrakis (4-carboxyphenyl) porphine (H2TCPP) and 550 mg benzoic acid, put them into a Pyrex bottle, add 2 mL of N,N-diethylformamide (DEF) and 5 drops of acetic acid, dissolve them by ultrasonic for two hours, put the Pyrex bottle into a 120°C constant temperature drying oven for 12 hours, cool to room temperature, and filter to obtain PCN-225 purple powder; wash the synthesized PCN-225 sample with ethanol for two hours, then wash with acetone, and then soak it in acetone for about 2 days, during which it is exchanged with fresh acetone once. Finally, centrifuge the mixture, and put the powder obtained by centrifugation into a constant temperature drying oven at 100°C for 10 hours. Cool and set aside.
[0045] S2. Use an electronic balance to weigh 4 mg of PCN-225 powder and place it in a beaker. Add 50 mL of deionized water, cover the beaker with plastic wrap, and place the beaker in an ultrasonic cleaner for 1 hour to obtain a uniform PCN-225 solution (PCN-225 mass fraction 0.008%). Then weigh 1 mg of organic europium Eu(DBM)3Bpy (DBM: dibenzoylmethane, Bpy: bipyridine) fluorescent powder, add it to the above PCN-225 solution, and ultrasonically disperse it uniformly for use.
[0046] S3. Weigh 0.75 g of sodium alginate and add it to the mixed solution of PCN-225 / Eu(DBM)3Bpy mentioned above, and add 0.5 mL of glycerol. Place it in a constant temperature magnetic stirrer at 80°C and stir it in a water bath for 1 hour to mix the solution evenly. Take it out and perform ultrasonic defoaming for standby use.
[0047] S4. Slowly pour 40mL of the mixed solution into a culture dish with a diameter of 140mm, and then place it horizontally in an electric constant temperature blast drying oven at 40℃ for 12h. After drying, take out the film and remove it to obtain the SA / PCN-225 / Eu(DBM)3Bpy composite film; put the film into a calcium chloride solution with a mass fraction of 2%, crosslink it for 10min, take it out and place it in a culture dish to dry for 30min, and obtain the SA / PCN-225 / Eu(DBM)3Bpy crosslinked composite indicator film.
[0048] S5. Prepare an ammonia solution with a concentration of 1%, and then pour it into a screw-mouth glass bottle. Then cut the indicator film prepared above into small squares of 1×1 cm, and use a thin wire to hang the film in a screw-mouth glass bottle filled with ammonia water, requiring that the film does not contact the ammonia solution and the bottle wall, and seal the glass bottle. After 1 hour, take out the film, place it under an ultraviolet lamp, take a photo and record it, use a color picker to measure the color of the original indicator film and the tested sample, and draw a color comparison card.
[0049] Example 2 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0050] The difference between this embodiment and embodiment 1 is that the mass of PCN-225 powder in step S2 is 2 mg (mass fraction 0.004%).
[0051] Example 3 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0052] The difference between this embodiment and embodiment 1 is that the mass of PCN-225 powder in step S2 is 6 mg (mass fraction 0.012%).
[0053] Example 4 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0054] The difference between this embodiment and embodiment 1 is that the mass of PCN-225 powder in step S2 is 8 mg (mass fraction 0.016%).
[0055] Example 5 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0056] The difference between this embodiment and embodiment 1 is that the mass of PCN-225 powder in step S2 is 10 mg (mass fraction 0.02%).
[0057] Example 6 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the mass fraction of calcium chloride in step S4 is 4%.
[0058] Example 7 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the mass fraction of calcium chloride in step S4 is 6%.
[0059] Example 8 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the mass fraction of calcium chloride in step S4 is 8%.
[0060] Example 9 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the mass fraction of calcium chloride in step S4 is 10%.
[0061] Example 10 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the concentration of ammonia water in step S5 is 0.25%.
[0062] Example 11 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the concentration of ammonia water in step S5 is 0.5%.
[0063] Example 12 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the concentration of ammonia water in step S5 is 0.75%.
[0064] Example 13 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film The difference between this example and Example 1 is that the concentration of ammonia water in step S5 is 1.25%.
[0065] Example 14 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0066] S1. Weigh 25 mg zirconium chloride (ZrCl4), 10 mg meso-tetrakis (4-carboxyphenyl) porphine (H2TCPP) and 550 mg benzoic acid, put them into a Pyrex bottle, add 2 mL of N,N-diethylformamide (DEF) and 5 drops of acetic acid, dissolve them by ultrasonic for two hours, put the Pyrex bottle into a 120°C constant temperature drying oven for 12 hours, cool to room temperature, and filter to obtain PCN-225 purple powder; wash the synthesized PCN-225 sample with ethanol for two hours, then wash with acetone, and then soak it in acetone for about 2 days, during which it is exchanged with fresh acetone once. Finally, centrifuge the mixture, and put the powder obtained by centrifugation into a constant temperature drying oven at 100°C for 10 hours. Cool and set aside.
[0067] S2. Use an electronic balance to weigh 4 mg of PCN-225 powder and place it in a beaker. Add 50 mL of deionized water, cover the beaker with plastic wrap, and place the beaker in an ultrasonic cleaner for 1 hour to obtain a uniform PCN-225 solution (mass fraction 0.008%). Then weigh 1 mg of organic europium Eu(DBM)3Bpy (DBM: dibenzoylmethane, Bpy: bipyridine) fluorescent powder, add it to the above PCN-225 solution, and ultrasonically disperse it uniformly for use.
[0068] S3. Weigh 0.75 g of sodium alginate and add it to the mixed solution of PCN-225 / Eu(DBM)3Bpy mentioned above, and add 0.5 mL of glycerol. Place it in a constant temperature magnetic stirrer at 80°C and stir it in a water bath for 1 hour to mix the solution evenly. Take it out and perform ultrasonic defoaming for standby use.
[0069] S4. Slowly pour 40mL of the mixed solution into a culture dish with a diameter of 140mm, and then place it horizontally in an electric constant temperature blast drying oven at 40℃ for 12h. After drying, take out the film and remove it to obtain the SA / PCN-225 / Eu(DBM)3Bpy composite film; put the film into a calcium chloride solution with a mass fraction of 2%, crosslink it for 10min, take it out and place it in a culture dish to dry for 30min, and obtain the SA / PCN-225 / Eu(DBM)3Bpy crosslinked composite indicator film.
[0070] S5. Choose fresh pure milk and pour 30 mL into a screw-mouth glass bottle. Cut the composite indicator film into small squares of 1 cm × 1 cm and hang the film in the screw-mouth glass bottle with a thin wire. The film should not touch the milk or the bottle wall. Seal and place at 20°C. Take it out every 12 hours and take photos to record the changes in the fluorescent color of the film, and draw a color comparison card.
[0071] Example 15 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0072] The difference between this embodiment and embodiment 14 is that in step S5, at 40° C., the film is taken out every 3 hours to take pictures and record the change of the fluorescent color, and a color comparison card is drawn.
[0073] Example 16 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0074] S1. Weigh 25 mg zirconium chloride (ZrCl4), 10 mg meso-tetrakis (4-carboxyphenyl) porphine (H2TCPP) and 550 mg benzoic acid, put them into a Pyrex bottle, add 2 mL of N,N-diethylformamide (DEF) and 5 drops of acetic acid, dissolve them by ultrasonic for two hours, put the Pyrex bottle into a 120°C constant temperature drying oven for 12 hours, cool to room temperature, and filter to obtain PCN-225 purple powder; wash the synthesized PCN-225 sample with ethanol for two hours, then wash with acetone, and then soak it in acetone for about 2 days, during which it is exchanged with fresh acetone once. Finally, centrifuge the mixture, and put the powder obtained by centrifugation into a constant temperature drying oven at 100°C for 10 hours. Cool and set aside.
[0075] S2. Use an electronic balance to weigh 4 mg of PCN-225 powder and place it in a beaker. Add 50 mL of deionized water, cover the beaker with plastic wrap, and place the beaker in an ultrasonic cleaner for 1 hour to obtain a uniform PCN-225 solution (mass fraction 0.008%). Then weigh 1 mg of organic europium phosphor Eu(DBM)3Bpy (DBM: dibenzoylmethane, Bpy: bipyridine) powder, add it to the above PCN-225 solution, and ultrasonically disperse it uniformly for use.
[0076] S3. Weigh 0.75 g of sodium alginate and add it to the mixed solution of PCN-225 / Eu(DBM)3Bpy mentioned above, and add 0.5 mL of glycerol. Place it in a constant temperature magnetic stirrer at 80°C and stir it in a water bath for 1 hour to mix the solution evenly. Take it out and perform ultrasonic defoaming for standby use.
[0077] S4. Slowly pour the mixed solution into a culture dish with a diameter of 140 mm, and then place it horizontally in an electric constant temperature blast drying oven at 40°C for 12 hours. After drying, take out the film and remove the film to obtain the SA / PCN-225 / Eu(DBM)3Bpy composite film; put the film into a calcium chloride solution with a mass fraction of 2%, crosslink it for 10 minutes, take it out and place it in a culture dish to dry for 30 minutes, and obtain the SA / PCN-225 / Eu(DBM)3Bpy crosslinked composite indicator film.
[0078] S5. Select fresh shrimps, wash them, remove the frontal horns and antennae, and put them in a screw-mouth glass bottle. Cut the composite indicator film into small squares of 1cm×1cm, and use a thin wire to hang the film sample in the screw-mouth glass bottle. The film should not touch the shrimp or the bottle wall. Put it in 20℃, take it out every 12 hours, take pictures and record the changes in the fluorescent color of the film, and draw a color comparison card.
[0079] Example 17 Preparation method and application of a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film
[0080] The difference between this embodiment and embodiment 16 is that in step S5, the film is taken out at room temperature of 40° C. every 3 hours to record the change in the fluorescence color of the film, and a color comparison card is drawn.
[0081] The morphology of the prepared PCN-225 powder was observed by scanning electron microscopy (SEM). Figure 2 ), Figure 2 a and Figure 2 b are pictures of PCN-225 powder magnified 2000 times and 5000 times respectively. It can be seen from the figure that the prepared PCN-225 is a rod-like structure with a rod length of 12 to 140 μm, a hexagonal cross-section, and a diameter of 15 to 35 μm. The structure of PCN-225 powder was analyzed by XRD ( Figure 3 ),from Figure 3 We can see that the X-ray diffraction peaks in the range of 10° to 30° are very sharp, indicating that the PCN-225 powder prepared in this patent has relatively good crystallinity. Compared with the XRD spectrum of the PCN-225 powder standard, the prepared PCN-225 powder has a higher diffraction peak at 14.45°, and the diffraction peaks in the range of 10° to 30° are basically corresponding to the X-ray diffraction peaks of the PCN-225 powder standard, proving that the PCN-225 powder has been successfully prepared. Figure 4 The infrared spectra of different samples are pure sodium alginate film, PCN-225 with a mass fraction of 0.020%, and the infrared absorption spectra of the indicator film and PCN-225 powder when the mass fraction of calcium chloride is 2% and 10%. It can be seen from the PCN-225 powder curve that the wave number is 3411cm -1 The peak is due to the stretching vibration of the intermolecular hydrogen bond OH bond; the wave number is 1600cm -1 、1580cm -1 、1500cm -1 、1450cm -1 The presence of four peaks of varying intensities indicates that the product is an aromatic compound; the wave number is 649 cm -1 The absorption peak at 3304cm is caused by the oscillation of hydrogen and oxygen in the plane, which further confirms the successful preparation of PCN-225 powder. The spectrum curve of pure sodium alginate film shows that the wave number is 3304cm -1 The peak value is due to the OH bond stretching absorption vibration absorption peak; the wave number is 1610cm -1 A broad peak appears at 1415 cm, which is due to the asymmetric stretching caused by the COO- group. -1 The peak is a narrow peak caused by symmetrical contraction; the wave number is 1021cm -1The peak at 3181cm is due to the stretching motion of CO. -1 The smoother part is due to the cross-linking of calcium ions and sodium alginate, and the stretching vibration of OH of carboxylic acid occurs, indicating the presence of sodium alginate. The addition of PCN-225 does not change the absorption peak of sodium alginate, and PCN-225 does not react chemically with the film.
[0082] The prepared PCN-225 powder was dispersed in different buffer solutions to observe the effect of pH buffer solution on the color development of PCN-225 ( Figure 5 ), the PCN-225 solution is lavender fluorescence in an acidic environment, and gradually turns pink fluorescence with the increase of pH, mainly because the degree of deprotonation of PCN-225 decreases with the increase of pH, resulting in a gradual increase in fluorescence. In an alkaline environment, the fluorescence gradually changes from pink to red. When the pH value of the buffer solution increases from 7 to 8, the fluorescence of the PCN-225 solution increases significantly. When the pH value of the buffer solution increases to 12, the fluorescence turns bright red, mainly because the degree of protonation of PCN-225 powder increases in an alkaline environment. At pH = 12, the molecular structure of PCN-225 changes, and bright red fluorescence appears. The fluorescence emission performance of PCN-225 in different pH buffer solutions was studied by fluorescence spectrophotometer ( Figure 6 ), the position of the fluorescence emission peak changes with the increase of the pH value of the buffer solution. As the pH value of the buffer solution increases from 2 to 11, the fluorescence emission wavelength does not change, but when the pH is equal to 12, the fluorescence band shifts to the red light region, and the position of the absorption peak changes from 639nm to 652nm, resulting in red fluorescence. The main reason is that in a strong alkaline environment, the molecular structure of PCN-225 changes, generating new substances, which leads to the shift of the fluorescence peak, which is also related to Figure 5 The color changes in correspondence.
[0083] In Examples 1-5, the mass fraction of PCN-225 in step S2 is different, and the other parameters remain unchanged. Controlling the mass fraction of PCN-225 will affect the mechanical properties and color development properties of the film. Figure 7The mechanical properties test results of the indicator film obtained at different PCN-225 mass fractions. With the increase of PCN-225 content, the tensile strength of the film first increases and then decreases; when the PCN-225 content increases from 0.004% to 0.012%, the elongation at break gradually increases; when the PCN-225 content increases from 0.012% to 0.020%, the elongation at break gradually decreases. The reason for the increase in tensile strength may be that the addition of PCN-225 forms hydrogen bonds with the film-forming matrix, which enhances the van der Waals force between molecules and makes the film more dense. The measurement results of elongation at break show that when a small amount of PCN-225 powder is added to the film, the film has good flexibility; when the content of PCN-225 continues to increase, it reduces the interaction between sodium alginate molecules, resulting in a decrease in the elongation at break of the film. Fig. 9 and Fig.10 The following is the color comparison of films obtained with different PCN-225 mass fractions under sunlight and ultraviolet light. Fig. 9 It can be seen that the film shows different colors under sunlight due to different PCN-225 contents in the film under natural air atmosphere (corresponding to the original sample). As the mass fraction of PCN-225 increases, the film changes from brown to reddish brown under sunlight. When these films are hung in a bottle of 1% ammonia for a period of time, the color of the film will gradually deepen under sunlight. When the mass fraction of PCN-225 in the film substrate is relatively low, the color change of the indicator film is more obvious. Fig.10 The color comparison of the indicator film obtained at different PCN-225 mass fractions under ultraviolet light. As can be seen from the figure, in a natural air atmosphere (corresponding to the original sample), as the PCN-225 mass fraction increases, the film changes from purple to purple-red under ultraviolet light, and the color gradually deepens. After these films are suspended in a bottle of 1% ammonia water for a period of time, the initial purple color of the film gradually turns into light purple-red under ultraviolet light. When the PCN-225 mass fraction in the film is 0.008%, the color change of the indicator film is more obvious.
[0084] In Examples 6-9, the mass fraction of calcium chloride in step S4 is different, and the other parameters remain unchanged. Different mass fractions of calcium chloride will affect the crosslinking degree of the film and thus affect the mechanical properties and color development properties of the film. Calcium ions, as a crosslinking agent in the composite film, can effectively increase the mechanical properties between materials. Figure 8The results of the test of the mechanical properties of the indicator film by the mass fraction of calcium chloride show that as the mass fraction of calcium chloride increases from 2% to 6%, the tensile strength of the film increases, and when the mass fraction of calcium chloride increases from 6 to 8%, the tensile strength of the film decreases; when the mass fraction of calcium chloride increases from 2% to 10%, the elongation at break of the film increases with the increase of the mass fraction of calcium chloride, but it does not increase linearly, but gradually becomes slow. The increase in the tensile strength of the film may be due to the low concentration of calcium ion cross-linking, which leads to the completion of cross-linking on the outside of the film, while the internal cross-linking of the film is incomplete, making the structure of the film different, resulting in an increase in tensile strength; the increase in the elongation at break of the film may be due to the increase in the concentration of calcium ion cross-linking, which increases the intermolecular force and improves the ductility of the film, thereby increasing the elongation at break. Fig.11 and Fig.12 This is a color comparison of the film obtained under different calcium chloride mass fractions under sunlight and ultraviolet light. Under sunlight, the film is in a natural air atmosphere (corresponding to the original sample), and as the mass fraction of calcium chloride increases, the color of the film changes from dark brown to light brown. When the film is suspended in a bottle of 1% ammonia for a period of time, the color of the film deepens under sunlight. Under ultraviolet light, the film is in a natural air atmosphere (corresponding to the original sample), and as the mass fraction of calcium chloride increases, the color of the film changes from purple to blue and then to purple. When the film is suspended in a bottle of 1% ammonia for a period of time, under ultraviolet light, the color of the film changes from purple to purple-red. When the mass fraction of calcium chloride is 10%, the color difference is the largest, and the color development effect of the film is the best at this time.
[0085] In Examples 10-13, the concentration of aqueous ammonia in step S5 is different, and the other parameters remain unchanged. Fig.13 The color performance of the composite indicator film in different concentrations of ammonia atmosphere is compared. The film appears purple under ultraviolet light in a natural air atmosphere (corresponding to the original sample). After the film is placed in a bottle with different concentrations of ammonia for a period of time, the indicator film shows a color response. When the ammonia concentration is as low as 0.25%, there is still an obvious color response, and the film changes from purple in the air atmosphere to purple-red in the ammonia atmosphere. Under the same placement time, as the ammonia concentration increases, the color change of the film increases, and the color difference also increases.
[0086] Examples 14-17 are application test examples of the indicator film in step S5, in which the film is placed at different temperatures (20°C and 40°C) and in different test objects (pure milk, fresh shrimp). In the milk test, at room temperature of 20°C, as the film is placed for an increased time, under ultraviolet light, the indicator film gradually changes from purple to purple-red, and as time goes by, the purple-red fluorescence becomes stronger and stronger; in an oven at 40°C, the film changes from purple to purple-red faster, and purple-red fluorescence can appear in a short time, and the fluorescence becomes brighter and brighter. In the shrimp freshness test, also at 40°C, the film changes color faster and the color change is most obvious, with the film changing from purple to purple-red within 3 hours; while at room temperature of 20°C, the indicator film changes color more slowly. The specific reason for the color change of the indicator film is that milk and shrimp are rich in protein. During the corruption process, microbial activity accelerates, and the protein and amino acids in the milk decompose, thereby releasing volatile nitrogen compounds and producing some volatile organic amines, ammonia and other alkaline gases, which cause the indicator film to change color. The color response is faster at 40°C because the higher the temperature, the faster the milk and shrimp deteriorate, and the faster and more obvious the color development. Fig.13 , Fig.14 and Fig.15 The results show that the prepared SA / PCN-225 / Eu(DBM)3Bpy composite indicator film can detect ammonia and the freshness of milk and shrimp. The promotion of SA / PCN-225 / Eu(DBM)3Bpy composite indicator film can not only monitor the freshness of food in real time and improve consumers' control over the freshness of food, but also bring more development opportunities to the food industry.
[0087] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.
[0088] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film, characterized in that: The preparation method comprises preparing PCN-225 powder by a hydrothermal method, activating PCN-225 powder, and preparing a sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film by a casting method; The hydrothermal method is used to prepare PCN-225 powder. A certain mass of zirconium chloride (ZrCl4), meso-tetrakis (4-carboxyphenyl) porphine (H2TCPP) and benzoic acid are weighed respectively, and a certain volume of N,N-diethylformamide (DEF) and acetic acid are added. After ultrasonic dissolution, the mixture is dried to obtain PCN-225 powder. The activated PCN-225 powder is washed with ethanol and acetone successively, and soaked in acetone, during which the acetone is replaced once, and then centrifuged and dried to obtain the activated PCN-225 powder; The tape casting method for preparing the SA / PCN-225 / Eu(DBM)3Bpy composite indicator film comprises the following steps: Step 1: prepare a PCN-225 solution, dissolve an appropriate amount of the activated PCN-225 powder in deionized water, and obtain a PCN-225 solution with a certain mass fraction after ultrasonic cleaning; Step 2: Prepare PCN-225 / Eu(DBM)3Bpy solution, weigh a certain amount of organic europium Eu(DBM)3Bpy (DBM: dibenzoylmethane, Bpy: bipyridine) fluorescent powder, add it to the PCN-225 solution in step 1, and disperse it evenly by ultrasonication; Step 3: Prepare SA / PCN-225 / Eu(DBM)3Bpy solution, weigh a certain amount of sodium alginate (SA) powder and add it to the PCN-225 / Eu(DBM)3Bpy solution in step 2, and add a small amount of glycerol, stir evenly, defoam and set aside; Step 4: Prepare SA / PCN-225 / Eu(DBM)3Bpy film, take an appropriate amount of SA / PCN-225 / Eu(DBM)3Bpy solution, dry it at 40°C for 12h, and then dry the prepared SA / PCN-225 / Eu(DBM)3Bpy film; Step 5: Prepare a high-strength, water-resistant SA / PCN-225 / Eu(DBM)3Bpy film. Place the SA / PCN-225 / Eu(DBM)3Bpy film described in step 4 into a calcium chloride solution with a certain mass fraction, take it out after a certain period of cross-linking reaction, and dry it to obtain a water-resistant SA / PCN-225 / Eu(DBM)3Bpy film.
2. The method for preparing the sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film according to claim 1, characterized in that: In step 1, the mass fraction of the PCN-225 solution is 0.004% to 0.02%.
3. The method for preparing the sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film according to claim 1, characterized in that: In step 3, the mass fraction of the sodium alginate is 0.5% to 3%.
4. The method for preparing the sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film according to claim 1, characterized in that: In step 5, the mass fraction of the calcium chloride solution is 2%-10%.
5. The method for preparing the sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film according to claim 1, characterized in that: The activated PCN-225 powder is immersed in acetone for about 48 hours, during which the acetone is replaced every 12 hours.
6. Application of the sodium alginate (SA) / PCN-225 / Eu(DBM)3Bpy composite indicator film prepared by the preparation method of claim 1, characterized in that: The application comprises the following steps: Step 1: Place the SA / PCN-225 / Eu(DBM)3Bpy composite indicator film in the same environment as the object to be tested, place it in the air without direct contact with the object to be tested, and record the color change of the indicator film at a temperature of 20°C to 40°C; Step 2: Take out the film in step 1 at regular intervals and photograph it under a fluorescent light to record the color changes.
7. The use of the sodium alginate (SA) / PCN-225 / Eu (DBM) 3Bpy composite indicator film according to claim 5, characterized in that: In step 1, the analyte is one of ammonia water, dairy products, and meat-derived foods.